Primary small cell carcinoma of the vagina: a rare instance of prolonged survival. Issue 3 (9th March 2019) - Kombathula, Sri Harsha; Rapole, Pragna Sagar; Prem, Shyama Sudha; Badhe, Bhawana
Abstract : Small cell carcinoma (SmCC) of the vagina is a rare and aggressive tumour. It comprises only 1% –2% of all gynaecological malignancies 85% of the patients with SmCC vagina die within a year of diagnosis. Here we report the case of a 65-year-old woman with stage III primary neuroendocrine carcinoma of vagina who was treated with chemoradiotherapy. The patient survived 1 year and 10 months after the initial presentation. SmCC of the vagina is very rare and despite being aggressive, the local disease can be controlled with a chemoradiation regimen.